Vol. 11 : Nanosystems Electrochemistry; Electrochemistry (2013, 2013)
Relaunching in 2012, the Specialist Periodical Report, Electrochemistry presents comprehensive and critical reviews in all aspects of the field. Specialist Periodical Reports present comprehensive and critical reviews of the current literature, with contributions from across the globe. Relaunching in 2012 with a new editorial team (Compton and Wadhawan) the eleventh volume of Electrochemistry has a special focus on Nanosystems. Uniquely, this series will include a review of Chinese literature - opening up this expanse of information to the rest of the word. Topics examined in this volume include: Nanopore systems, metal organic frameworks, nanoparticles, nanocarbon electrochemistry, bipolar electrochemistry in nanosscience and electrochemistry with liquid nanosystems. This volume is a key reference in the field of electrochemistry, allowing the reader to easily become aquainted with the lastest research and opinion. Purchasers of the print edition can register for free access to the electronic edition by returning the enclosed registration card.